Summary of drug therapy to treat cognitive impairment-induced obstructive sleep apnea - He, Daqiang; Chen, Jian; Du, Xiaoxue; Xu, Linhao (Frontiers in Cellular Neuroscience, 2023)
Obstructive sleep apnea (OSA) is a severe sleep disorder associated with intermittent hypoxia and sleep fragmentation. Cognitive impairment is a significant and common OSA complication often described in such patients. The most commonly utilized methods in clinical OSA treatment are oral appliances and continuous positive airway pressure (CPAP). However, the current therapeutic methods for improving cognitive function could not achieve the expected efficacy in same patients. Therefore, further understanding the molecular mechanism behind cognitive dysfunction in OSA disease will provide new treatment methods and targets. This review briefly summarized the clinical manifestations of cognitive impairment in OSA disease. Moreover, the pathophysiological molecular mechanism of OSA was outlined. Our study concluded that both SF and IH could induce cognitive impairment by multiple signaling pathways, such as oxidative stress activation, inflammation, and apoptosis. However, there is a lack of effective drug therapy for cognitive impairment in OSA. Finally, the therapeutic potential of some novel compounds and herbal medicine was evaluated on attenuating cognitive impairment based on certain preclinical studies.